Everyday engineering : an ethnography of design and innovation. - Vinck, Dominique, ....- (Cambridge : MIT Press, 2009)
Everyday Engineering was written to help future engineers understand what they are going to be doing in their everyday working lives, so that they can do their work more effectively and with a broader social vision. It will also give sociologists deeper insights into the sociotechnical world of engineering. The book consists of ethnographic studies in which the authors, all trained in both engineering and sociology, go into the field as participant-observers. The sites and types of engineering explored include mechanical design in manufacturing industries, instrument design, software debugging, environmental management within companies, and the implementation of a system for separating household waste. The book is organized in three parts. The first part introduces the complexity of technical practices. The second part enters the social and cultural worlds of designers to grasp their practices and motivations. The third part examines the role of writing practices and graphical representation. The epilogue uses the case studies to raise a series of questions about how objects can be taken into account in sociological analyses of human organizations.